2020
DOI: 10.1186/s10020-020-0137-7
|View full text |Cite
|
Sign up to set email alerts
|

The association of CASC16 variants with breast Cancer risk in a northwest Chinese female population

Abstract: Purpose: Genetic variants play a critical role in the development of breast cancer. This investigation aimed to explore the association between CASC16 polymorphisms and breast cancer susceptibility. Methods: We conducted a case-control study of 681 patients and 680 healthy individuals to investigate the correlation of five SNPs with breast cancer in a Northwest Chinese female population. Odds ratios (OR) and 95% confidence intervals (CIs) were used to assess the association. Results: Our study found that rs478… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…However, the same findings of perineural invasion and histological grade were not found in other studies. In addition, Zuo et al (2020) and Sun et al (2020) found that there was a significant association between rs4784227 and lymph node metastasis status, but this conclusion was not reached in our study. We propose that this may be because the number of people who carried the TT genotype in our sample was small.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…However, the same findings of perineural invasion and histological grade were not found in other studies. In addition, Zuo et al (2020) and Sun et al (2020) found that there was a significant association between rs4784227 and lymph node metastasis status, but this conclusion was not reached in our study. We propose that this may be because the number of people who carried the TT genotype in our sample was small.…”
Section: Discussioncontrasting
confidence: 90%
“…In our study, we found that the T allele was the minor allele of rs4784227 , and the distribution of alleles and genotypes of SNP rs4784227 ( C = 69.93%, T = 30.07%, CC =48.43%, CT = 43.00%, TT = 8.57%) was consistent with current research. The results indicated that those who carried the T allele had high BC susceptibility, which was in line with Zuo et al (2020) , Tajbakhsh et al (2019) and He et al (2014) . In our study, the best-fitting inheritance model of rs4784227 was the dominant model, and in this model, we found that the CC genotype of SNP rs4784227 provided a protective effect against BC, which was consistent with Zuo et al (2020) and Tajbakhsh et al (2019) .…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations